Reflections on Combating Corruption Crimes at the International Level (Al-Mukhtar Journal of Legal Science, 2025)
Combating corruption is essentially an international process reflected in legislation at the national level. Therefore, this research contribution attempts to provide a panoramic picture of the concept of corruption at the international level and the efforts related to combating it in this field. Researching the origins of things is the best way to understand them, identify the objectives they have, and know specifically what we want to gain from joining international arsenals related to combating corruption. Do we need to adopt all these international arrangements in order to prevent and prosecute corruption crimes? This raises a fundamental problem in the possibility of borrowing these efforts by countries that have never known a true democratic life. Will borrowing these arrangements bear fruit and will they be useful, or is it simply a matter of adopting international arrangements like this without understanding them or even digesting them before borrowing them?
Keywords: crime; Anti-Corruption; international law